Combretastatin-based compounds with therapeutic characteristics: a patent review. (2nd September 2019) - Nainwal, Lalit Mohan; Alam, Mohammad Mumtaz; Shaquiquzzaman, Mohammad; Marella, Akranth; Kamal, Ahmed
ABSTRACT: Introduction : Combretastatins represent a potent class of phenolic-stilbene natural products that function as colchicine binding site inhibitors of tubulin polymerization and have been advanced as promising anticancer lead compounds. Among them, combretastatin A-4 is the most potent lead molecule due to its broad spectrum cytotoxicity against a variety of tumors. However, low water solubility due to its high lipophilic nature and inter-conversion of olefinic double bond from more active cis to less active trans- conformation poses limitations to its clinical utility. However, different approaches including prodrugs, salt formations, structural modifications, prevention of inter-conversion of the olefinic bond and changes to the substitution pattern on the rings of combretastatin A-4 were investigated and successfully resulted in different combretastatin-based molecules that demonstrated varying levels of potency against different types of tumors during their in-vitro and in-vivo studies. Areas covered : This review covers the patents over a period of 2008–2018. Expert opinion : Molecular hybridization and prodrug designing imparted multi-targeted actions to combretastatin derivatives. Currently, various combretastatin derivatives are under clinical trials. These derivatives could be used to treat disorders other than cancer, due to their vascular disrupting action.